MyoMed205 counteracts titin hyperphosphorylation and the expression of contraction-regulating proteins in a rat model of HFpEF - Vahle, Beatrice; Schauer, Antje; Augstein, Antje; Jarabo, Maria-Elisa Prieto; Friedrich, Janet; Barthel, Peggy; Männel, Anita; Mangner, Norman; Labeit, Siegfried; Bowen, T. Scott; Linke, Axel; Adams, Volker (Journal of cachexia, sarcopenia and muscle, 2025)
Background Heart failure with preserved ejection fraction (HFpEF) is associated with exercise intolerance, accompanied by alterations in the peripheral skeletal muscle (SKM). We have recently shown that titin, a giant sarcomere protein, is hyperphosphorylated in HFpEF. MuRF1 is a muscle-specific ubiquitin E3-ligase that interacts with titin. Blocking this interaction via small molecules (MyoMed205) can improve muscle function and mitochondrial activity in HFpEF. This study aimed to investigate the impact of MyoMed205 on titin phosphorylation and its association with changes in muscle structure and function. Methods Obese ZSF1 rats with established HFpEF received rat chow with (n = 15) or without (n = 15) MyoMed205 and were compared with lean littermates (n = 15), serving as controls. After 12 weeks, in vitro SKM force, atrophy and titin—as well as contractile protein expression—were evaluated (soleus and extensor digitorum longus [EDL]). Statistical analysis was performed via multiple unpaired t-test or one-way ANOVA. Results In HFpEF, titin hyperphosphorylation by 13% in the EDL (p = 0.09) and 14% (p = 0.03) in the soleus muscle was evident. This hyperphosphorylation was driven in part by an increase in S11878 phosphorylation (EDL: +68%, p = 0.004; Sol: +23.8%, p = 0.03), which was linked to myofiber atrophy (r = −0.68, p = 0.006) and a decline in maximal specific muscle force (r = −0.54, p = 0.008). In the EDL, significant changes in protein expression related to atrophy (MuRF1 [+24.9%, p = 0.02], GDF8 [+20.6%, p = 0.09]) and calcium handling (slow troponin C [−46%, p = 0.02], fast troponin I [+35.8%, p = 0.02]) were found in HFpEF. All of the above-mentioned effects in HFpEF were almost completely abolished by MyoMed205 treatment, and significantly elevated titin expression was visible (+19.7%, pcon = 0.04, pHFpEF = 0.01). Conclusions Titin hyperphosphorylation may negatively impact skeletal muscle integrity and function in HFpEF. MyoMed205 reduced titin hyperphosphorylation and was associated with preserved skeletal muscle function and mass. Further studies are necessary to confirm the direct role of titin hyperphosphorylation on muscle function and to evaluate the therapeutic potential of MyoMed205 in HFpEF.
Gesehen am 10.09.2025